Interfaith Marriage: A Perspective of Law Number 1 of 1974 - Khairun Na’im; Faisal Sadat Soaduon Harahap; Dahris Siregar (Journal of Law Science, 2024)
Indonesian society has many different ethnicities, races, and religions, interfaith marriage became a recent practice. According to Marriage Legislation 16th of 2019, which amends the 1974 Law No. 1, should the bride and groom's respective faiths forbid marriage, then there is no law permitting a marriage between two potential brides who practise different religions. In this study, it observes how marriages of different religions are regulated by Indonesian marriage law, what makes the marriage law different in terms of religion and what the legal consequences are. The study's research technique was normative legal research. The statutory method is used, or the statute approach, and descriptive research is used. Secondary data gathered from public documents and literary studies in the form of books or documentation are the types and sources of data used. Research shows that marriage between as to the 1974 Marriage Law No. 1, it is forbidden to marry persons of different faiths. Because marriages of different religions not fulfil the legal prerequisites for marriage as outlined in the provisions. To determine invalid marital status, none of the conditions mentioned refer under Law No. 1 of 1974's Article 2, that regulates matrimony. Children born from marriages of different religions are considered illegitimate and cannot inherit from their fathers.